Inversion evolutionary rates might limit the experimental identification of inversion breakpoints in non-model species - Eva Puerma (Nature Portfolio, 2017)
Abstract Chromosomal inversions are structural changes that alter gene order but generally not gene content in the affected region. In Drosophila, extensive cytological studies revealed the widespread character of inversion polymorphism, with evidence for its adaptive character. In Drosophila subobscura, polymorphism affects both its four large autosomal elements and its X (A) chromosome. The characterization of eight of these autosomal inversions breakpoints revealed that most of them originated through the staggered-breaks mechanism. Here, we have performed chromosomal walks to identify the breakpoints of two X-chromosome widely distributed inversions —A2 and A1— of D. subobscura. Inversion A2 is considered a warm-adapted arrangement that exhibits parallel latitudinal clines in the species ancestral distribution area and in both American subcontinents, whereas inversion A1 is only present in the Palearctic region where it presents an east-west cline. The duplication detected at the A2 inversion breakpoints is consistent with its origin by the staggered-breaks mechanism. Inversion A1 breakpoints could not be molecularly identified even though they could be narrowly delimited. This result points to chromosome walking limitations when using as a guide the genome of other species. Limitations stem from the rate of evolution by paracentric inversions, which in Drosophila is highest for the X chromosome.